2017
DOI: 10.1016/j.jelechem.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrolytes on redox potentials through ion pairing

Abstract: Reduction potentials have been determined for two molecules, benzophenone (BzPh) and perylene (Per), effectively in the complete absence of electrolyte as well as in the presence of three different supporting electrolytes in the moderately polar solvent THF. A description of how this can be so, and qualifications, are described in the discussion section. The primary tool in this work, pulse radiolysis, measures electron transfer (ET) equilibria in solution to obtain differences in redox potentials. Voltammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Voltammograms of the standard are recorded before and after each set of measurements. From the dependence of E (1/2) on the electrolyte concentration, the potential for each neat solvent is estimated from extrapolation to zero electrolyte concentration. This method for extrapolation of E (1/2) to zero concentration, however, does not account for potential aggregation with dissociation constants lower than the mM range …”
Section: Methodsmentioning
confidence: 99%
“…Voltammograms of the standard are recorded before and after each set of measurements. From the dependence of E (1/2) on the electrolyte concentration, the potential for each neat solvent is estimated from extrapolation to zero electrolyte concentration. This method for extrapolation of E (1/2) to zero concentration, however, does not account for potential aggregation with dissociation constants lower than the mM range …”
Section: Methodsmentioning
confidence: 99%
“…Recent pulse radiolysis studies have shown that even “inert” electrolytes can stabilize redox-active ions by hundreds of millivolts. 23 25 These examples highlight the need to develop a stronger understanding of how noncovalent interactions affect the kinetics and thermodynamics of electron transfer, and more broadly, any reaction where ion stabilization impacts reactivity. …”
Section: Introductionmentioning
confidence: 99%
“…With surface confined voltammetry, widespread comparisons of parameterisation outcomes with various electron transfer models, as well as Langmuir, Temkin of Frumkin isotherms, could be invaluable. Another issue usually overlooked in modelling even a simple electron transfer step is the change in ion pairing [27,28] that almost inevitably accompanies an electrode process. Ion pairing is particularly favoured under voltammetric conditions because the supporting electrolyte concentration is commonly at least 0.1 M and hence in large excess over the mM or lower concentration of the species assumed to undergo a simple oxidation or reduction reaction in the modelling.…”
mentioning
confidence: 99%